Microelectrodes with gold nanoparticles and self-assembled monolayers for in vivo recording of striatal dopamine - Tsai, Tien-Chun (2013)
Electrochemical determination of in vivo dopamine (DA) using implantable microelectrodes is essential for monitoring the DA depletion of an animal model of Parkinson's disease (PD), but faces substantial interference from ascorbic acid (AA) in the brain area due to similar electroactive characteristics. This study utilizes gold nanoparticles (Au-NPs) and self-assembled monolayers (SAMs) to modify platinum microelectrodes for improving sensitivity and specificity to DA and alleviating AA interference. With appropriate choice of ω-mercaptoalkane carboxylic acid chain length, our results show that a platinum microelectrode coated with Au-NPs and 3-mercaptopropionic acid (MPA) has approximately an 881-fold specificity to AA. During amperometric measurements, Au-NP/MPA reveals that the responsive current is linearly dependent on DA over the range of 0.01–5 μM with a correlation coefficient of 0.99 and the sensitivity is 2.7-fold that of a conventional Nafion-coated electrode. Other important features observed include fast response time (below 2 s), resistance to albumin adhesion and low detection limit (7 nM) at a signal to noise ratio of 3. Feasibility of in vivo DA recording with the modified microelectrodes is verified by real-time monitoring of electrically stimulated DA release in the striatum of anesthetized rats with various stimulation parameters and administration of a DA uptake inhibitor. The developed microelectrodes present an attractive alternative to the traditional options for continuous electrochemical in vivo DA monitoring.